2013
DOI: 10.1073/pnas.1313223110
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of smooth muscle and cartilage juxtaposition in the developing mouse upper airways

Abstract: In the trachea and bronchi of the mouse, airway smooth muscle (SM) and cartilage are localized to complementary domains surrounding the airway epithelium. Proper juxtaposition of these tissues ensures a balance of elasticity and rigidity that is critical for effective air passage. It is unknown how this tissue complementation is established during development. Here we dissect the developmental relationship between these tissues by genetically disrupting SM formation (through Srf inactivation) or cartilage form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
124
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(133 citation statements)
references
References 35 publications
8
124
0
1
Order By: Relevance
“…In peripheral lung, Wnt7b and Wnt2 play essential roles in establishment of vascular and airway smooth muscle (Cohen et al, 2009; Goss et al, 2011). In our model, deletion of Wls from the epithelium of the trachea resulted in expansion of muscle layer into the ventral aspect of the trachea findings not seen in other experimental models of tracheomalacia (Hines et al, 2013; Turcatel et al, 2013). Our studies showed that deletion of Sox9 from tracheal mesenchyme using the Col2a1Cre mice caused severe loss of cartilage; however, expansion of αSMA staining into the ventral side of the trachea was not observed (Fig.6).…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…In peripheral lung, Wnt7b and Wnt2 play essential roles in establishment of vascular and airway smooth muscle (Cohen et al, 2009; Goss et al, 2011). In our model, deletion of Wls from the epithelium of the trachea resulted in expansion of muscle layer into the ventral aspect of the trachea findings not seen in other experimental models of tracheomalacia (Hines et al, 2013; Turcatel et al, 2013). Our studies showed that deletion of Sox9 from tracheal mesenchyme using the Col2a1Cre mice caused severe loss of cartilage; however, expansion of αSMA staining into the ventral side of the trachea was not observed (Fig.6).…”
Section: Discussionmentioning
confidence: 39%
“…A recent study proposed that the precise apposition of chondroblasts and myoblasts establishes the boundaries between cartilage and muscle, thus generating a structure needed for rigidity and flexibility characteristic of the trachea (Hines et al 2013). It is presently unclear how dorsal-ventral patterning of developing tracheal mesenchyme is established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these data indicate that Ezh2 regulates the temporal and spatial patterning of the basal cell lineage in the mouse lung. A recent report showed that Trp63+ basal cells were enriched on the side of the trachea that developed cartilaginous rings during development (Hines et al, 2013). Loss of cartilage in the lung mesenchyme leads to a loss of Trp63+ basal cells, suggesting an important mesenchymal-epithelial cross-talk that regulates basal cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, any perturbation in the stereotyped pattern of smooth muscle differentiation also prevented terminal bifurcation of the epithelium. Since transgenic knockout of smooth muscle is embryonic lethal (Hines et al, 2013), organ-specific genetic modulations will be required for definitive understanding of the role for visceral smooth muscle in epithelial morphogenesis.…”
Section: Discussionmentioning
confidence: 99%